Evaluasi Inovasi Prioritas Smart City Di Kabupaten Bandung Barat Menggunakan Metode Fuzzy Logic - Rizky Fajar Ramdhani Ramdhani; Hady Sofyan; Rani Sri Wahyuni (Sekolah Tinggi Teknologi Wastukancana, 2025)
This study aims to assess the implementation of smart city innovations in West Bandung Regency in 2024, utilizing a fuzzy logic-based approach. Unlike previous research, which relied on the Unified Theory of Acceptance and Use of Technology (UTAUT) model, this study employs fuzzy logic techniques to evaluate user satisfaction with 37 prioritized innovative city applications. Fuzzy logic is selected for its capability to process qualitative and subjective data, enabling a more adaptive assessment of user perceptions. Data were gathered through structured questionnaires and in-depth interviews with public service employees, who are the primary users of these digital platforms. Evaluation dimensions—including ease of use, perceived benefits, social influence, and facility availability—were translated into fuzzy sets and analyzed through a Mamdani fuzzy inference system to derive comprehensive satisfaction scores. The results reveal that the “Smart Branding: Visit KBB” and “BA QRIS” applications achieved the highest satisfaction levels, particularly in terms of usability and infrastructure support. The study offers fuzzy logic-based recommendations to enhance the effectiveness, acceptance, and strategic development of smart city innovations. It also proposes an alternative, more responsive evaluation method for policy-making in the context of digital governance. Keyword: smart city, fuzzy logic, user satisfaction, innovation, West Bandung Regency